The Effect of Disaster Simulation on Earthquake Disaster Knowledge on Students at SDN Inpres Silae - Wendi Muhammad Fadhil; Ahmil; Yunita Larasati (Journal of sciences and health, 2022)
Background: Children are the most vulnerable group to become victims of the earthquake. Therefore, they really need to be equipped with the concept of earthquakes, earthquake hazards and earthquake disaster mitigation by simulating earthquake disasters. This study aims to determine the effect of disaster simulation on knowledge of earthquake disasters in students at SDN Inpres Silae. Methods: This type of research is quantitative with a pre-experimental research design and uses a one-group pre-test-post-test approach. The total population is 39 students with the sampling technique of cluster sampling with a sample of 34 students. Data analysis using Wilcoxon test. Results: There is a difference in knowledge before and after the disaster simulation, the pretest in the moderate category is 58.8%, and the posttest in the good category is 88.2%. The data before and after the simulation were compared, the percentage increase in the good category increased by 65%, and the moderate category decreased by 40% after the simulation was carried out, and in the less category it was no longer found after the simulation was carried out. The results of the analysis obtained P Value 0.000 which means P Value 0.05. Conclusion: There is an effect of earthquake disaster simulation on knowledge of earthquake disaster on students at SDN Inpres Silae. Keywords: Disaster simulation, knowledge, earthquake